A Novel Cryo-controlled Growth Technique for High Performance Organometal Halide Perovskite Solar Cells - Ng, Annie; Ren, Zhiwei; Shen, Qian; Cheung, Sin Hang; Djurišić, Aleksandra B.; Su, Shu Kong; Li, Gang; Surya, Charles (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems, 2018)
The recent trend of the high-performance perovskite solar cell (PSC) is based on multi-component perovskite materials. The reproducible perovskite growth techniques are crucial for acquiring mixed halide perovskite films with precise stoichiometry, desirable morphology, and low defect density.
Keywords: perovskite solar cell (PSC); Power conversion efficiency (PCE)